The book of Esther between Judaism and Christianity: the biblical story, self-identification, and antisemitic interpretation - Kalimi, Isaac (Cambridge University Press, 2023)
Explores different traditions and usage of Esther in Judaism and Christianity, without neglecting the fundamental questions in scholarship.